Water Insecurity in Coastal Bangladesh: A Gender Equality and Social Inclusion (GESI) Perspective - Joshi, Deepa; Sarker, Mou Rani; Basnet, Sahara (CGIAR System Organization, 2024)
With the increasing feminization of agriculture, women are taking on greater roles and responsibilities in agricultural labor, leading to heightened dependence on water resources. While women’s water challenges are often framed as being limited to domestic use, and productive water use is typically attributed to men, this assumption generalizes the issue. Research on gender and water has predominantly focused on domestic water, sanitation, and hygiene, leaving the intersection of gender and productive water use underexplored. This study seeks to fill this gap by examining the complexities of both agricultural (productive) and domestic water insecurity through an intersectional lens, considering differences across gender, class, land ownership, age, and social identity. We employed the IWISE (Individual Water Insecurity Experience) Scales and the AgWISE (Agricultural Water Insecurity Experience) module to assess water insecurity among 800 individuals in southern coastal Bangladesh.